Attachment in OCD: A meta-analysis. (March 2020) - van Leeuwen, W.A.; van Wingen, G.A.; Luyten, P.; Denys, D.; van Marle, H.J.F.
Highlights: Both attachment anxiety and attachment avoidance are associated with OCD (symptoms). No differences were found between clinical and non-clinical populations. These findings support attachment approaches to OCD. Combining cognitive and attachment-based strategies may improve OCD treatment. Abstract: Introduction: It has been proposed to extend the cognitive-behavioural model of obsessive-compulsive disorder (OCD) with attachment theory to shed light on the affective and developmental factors underlying the disease. With a growing number of empirical studies on the subject, this meta-analysis aims to quantify a possible relationship between attachment insecurity and OCD. Methods: A systematic search was conducted for studies in adult populations of patients with OCD as well as general populations displaying symptoms of OCD. Effect sizes of attachment anxiety and attachment avoidance were calculated separately. Covariates of demographic variables were used in meta-regressions. Results: Sixteen studies were included. Meta-analyses showed an association of medium to large effect size (Hedges' g = 0.69; 95 % CI 0.58 – 0.80; p < 0.001) between OCD and attachment anxiety, and an association of medium effect size (Hedges' g = 0.47; 95 % CI 0.39 – 0.54; p < 0.001) between OCD and attachment avoidance. Effect sizes in OCD population and general population studies did not differ significantly. Discussion: Robust effect sizes of both attachment anxiety and avoidance in relation to OCD symptomatology corroborate an attachment-centred view of OCD. These findings furthermore suggest that integrating cognitive and attachment-based therapeutic approaches to OCD may benefit patients in which developmental or emotional factors hinder successful treatment.